1992
DOI: 10.1001/archinte.1992.00400210040007
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Pneumonia in Adult Hospitalized Patients Infected With the Human Immunodeficiency Virus

Abstract: The HIV-infected patient is at increased risk for pneumococcal pneumonia and bacteremia. Patients younger than 40 years of age who present with pneumococcal pneumonia should be considered for HIV testing, since it may be the first manifestation of HIV infection. Specific antimicrobial therapy is curative in the majority of HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 18 publications
0
14
2
Order By: Relevance
“…Indeed, this proportion may be an underestimate because we assumed that patients without medical-record documentation of HIV infection were HIV-uninfected. Prior work has demonstrated that HIV-infected patients are at a significantly higher risk of developing bacteremic pneumococcal pneumonia than is the general population [34][35][36]. However, in this study, HIV infection was not a risk factor for infection with a penicillin-nonsusceptible isolate (table 1).…”
Section: Discussioncontrasting
confidence: 60%
“…Indeed, this proportion may be an underestimate because we assumed that patients without medical-record documentation of HIV infection were HIV-uninfected. Prior work has demonstrated that HIV-infected patients are at a significantly higher risk of developing bacteremic pneumococcal pneumonia than is the general population [34][35][36]. However, in this study, HIV infection was not a risk factor for infection with a penicillin-nonsusceptible isolate (table 1).…”
Section: Discussioncontrasting
confidence: 60%
“…In particular, there were lower levels of initial WBC count and serum albumin in the HIV-seropositive patients. Although these two parameters have previously been noted by some investigators 16,17,19,22,24,25 to be important negative prognostic factors in pneumococcal bacteremia (being present more commonly in patients who require ICU admission or in patients who died), their presence in the HIV-seropositive patients in our study was not associated with a worse outcome. This may simply reflect a statistical analysis that was performed with a small number of patients; however, it is important to note that although the overall WBC count in our HIV-seropositive group was lower than that of the HIV-seronegative group, only three patients actually had leukopenia, one of whom died.…”
Section: Discussioncontrasting
confidence: 58%
“…There appeared to be more multilobar consolidation among our HIV-seropositive patients, but this difference did not quite reach statistical significance. While some investigators 16 have noted a difference in the radiologic appearance of AIDS patients with bacteremic pneumococcal pneumonia compared with HIV-seropositive patients without AIDS and HIV-seronegative individuals (such patients being more likely to have bilateral infiltrates), other investigators 9,16,24 have found no differences when comparing the radiologic findings in HIV-seropositive and HIV-seronegative patients alone.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has also been noted in U.S. and Spain and for this reason, we agree that young patients presenting with an episode of invasive pneumococcal infection should be screened for co-existing HIV infection. 12,28 The pneumococci isolated from HIV patients demonstrated significantly less antibiotic resistance than isolates from the non-HIV patients (Table 4). This may be due to the fact that fewer South African patients had been diagnosed as having pneumonia previously and/or received antibiotics in the past 3 months, known risk factors for pneumococcal antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%